Structural design and preparation method of in-vivo controllable degradation and metabolism up-conversion fluorescence nanoprobe
By designing upconverted fluorescent nanoprobes of core-shell-shell structures, the problem of difficult degradation of traditional nanoparticles in the biological environment is solved, and the biocontrollable degradation and metabolism of nanoprobes is achieved, which improves the fluorescence brightness and stability, and is suitable for long-term biological imaging.
Patent Information
- Application Number
- CN202510040285.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-15
AI Technical Summary
Traditional inorganic lanthanide-doped fluoride upconversion fluorescent nanoparticles are difficult to degrade in biological environments, resulting in prolonged retention in biological tissues and potentially toxicity.
A live controlled degradation and metabolic up-conversion fluorescent nanoprobe with a core-shell-shell structure was designed. The core layer was fluoride nanoparticles doped with rare earth element activator, the inner shell was doped with rare earth sensitizer and zirconium elements, and the outer shell was a alkaline earth metal fluoride doped with zirconium element. The nanoprobe was controlled degraded in a living water environment through zirconium element doping.
The biocontrollable degradation and metabolism of nanoprobes is achieved, which avoids the potential side effects of long-term accumulation in the organism, and at the same time improves the fluorescence brightness and stability, which is suitable for long-term biological imaging.
Smart Images

Figure CN119823760A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the fields of up-conversion fluorescence and nanomaterial technology, and in particular to a structural design and preparation method of a living body controllable degradation and metabolic up-conversion fluorescence nanoprobe. Background Art
[0002] Upconversion fluorescence imaging has the advantages of no photobleaching and deep penetration into biological tissues, and is particularly suitable for optical imaging of long-term and deep biological tissues. Upconversion fluorescence nanoprobes are the key material basis for determining the quality of upconversion optical bioimaging. In recent years, inorganic fluorescent nanoparticles doped with rare earth ions (such as NaYF4, CaF2, etc.) have been rapidly developed due to their strong chemical stability, low phonon energy, excellent upconversion optical properties, strong resistance to fluorescence bleaching, and near-infrared excitation. However, in practical applications, surface defects of nanoprobes can cause the fluorescence quenching effect of rare earth ions, resulting in a significant reduction in the upconversion fluorescence intensity. It is necessary to cover the surface of the nanoparticles with an inert shell to suppress surface defects. The size of the coated nanoparticles is often much larger than the limit (5.5nm) that can pass through the glomerular filtration of the organism, which makes it difficult for traditional inorganic upconversion nanoparticles to be rapidly metabolized by the kidneys, and they are easily retained in the organs of the organism for a long time, which may have adverse effects on the organism. In order to make the upconversion fluorescent probe degrade in the living environment, rare earth ion doped fluorine zirconate (K3ZrF7, Na3ZrF7) nanoparticles were developed. Compared with the traditional fluoride matrix, the zirconium element in the fluorine zirconate can reduce the stability of the probe matrix, so that the nanoparticles can be degraded in the living environment. However, there are two main problems with these two fluorine zirconate materials as upconversion nanoprobes. First, the content of zirconium is fixed. K3ZrF7 and Na3ZrF7 degrade quickly in the biological environment and the degradation rate is uncontrollable. The fluorescence degradation rate of the upconversion nanoprobe is fast, which is not suitable for long-term biological imaging processes; second, the transition metal zirconium element will produce cross-relaxation phenomenon on rare earth ions, resulting in low upconversion brightness of the nanoprobe and limited upconversion spectral emission characteristics. Summary of the invention
[0003] The technical problem to be solved by the present invention is to overcome the above technical defects and provide a structural design and preparation method of a living in vivo controllable degradation and metabolic upconversion fluorescent nanoprobe aimed at solving the problem that traditional inorganic lanthanide-doped fluoride upconversion fluorescent nanoparticles are not metabolizable in biological environments, such nanoparticles are difficult to be effectively eliminated through biological metabolic pathways, and may cause long-term retention and toxicity in biological tissues.
[0004] To solve the above technical problems, the technical solution provided by the present invention is: a living controllable degradation and metabolic upconversion fluorescent nanoprobe structure design, including a core layer, an inner shell layer and an outer shell layer, with a particle size less than 100nm; the core layer is a nanoparticle structure, the inner shell layer is an alkaline earth metal fluoride with a rare earth sensitizer and zirconium element, and the outer shell layer is an alkaline earth metal fluoride with zirconium element.
[0005] Preferably, the nanoparticle structure comprises cubic phase NaYF4 or NaLuF4 fluoride nanoparticles doped with a rare earth element activator, and the particle size is less than 5.5 nm.
[0006] Preferably, the rare earth element activator is one or a combination of ytterbium, thulium, holmium, erbium and praseodymium.
[0007] Preferably, the inner shell matrix is one or a combination of cubic calcium fluoride, strontium fluoride or barium fluoride;
[0008] The inner shell rare earth sensitizer is one or a combination of ytterbium or neodymium.
[0009] Preferably, when the core layer covers the inner shell layer, double-layer particles are formed with a particle size of 8 to 20 nm.
[0010] Preferably, the outer shell layer is one or a combination of cubic calcium fluoride, strontium fluoride or barium fluoride.
[0011] When the outer shell layer covers the double-layer particles, triple-layer particles are formed with a particle size of 10 to 100 nm.
[0012] Another aspect of the present invention discloses: a method for preparing a living body controllable degradation and metabolic upconversion fluorescent nanoprobe structure design, comprising the following steps:
[0013] (a): Disperse metal fluoride in liquid:
[0014] The metal fluoride is a mixture of NaF or NaOH and NH4F, and the liquid is an anhydrous mixed solution of oleic acid, oleylamine and 1-octadecene;
[0015] (b): Dispersing the rare earth compound in a solvent:
[0016] The rare earth compound is one or more of Ln(CF3COO)3, Ln(CH3COO)3, LnCl3, wherein (Ln=Yb, Er, Tm, Ho);
[0017] The solvent is an anhydrous mixed solution of oleic acid, oleylamine and 1-octadecene;
[0018] (c): heating the liquid obtained in (b) and hot-injecting the liquid obtained in (a) at high temperature to obtain rare earth activator-doped core layer nanoparticles after reaction;
[0019] (d) Dispersing the sensitizer trifluoroacetate, alkaline earth metal trifluoroacetate and zirconium acetate in a liquid:
[0020] The sensitizer trifluoroacetate is Ln(CF3COO)3(Ln=Yb,Nd), the alkaline earth metal trifluoroacetate is M(CF3COO)2(M=Ca,Sr,Ba), the chemical formula of zirconium acetate is: Zr(CH3COO)4, and the liquid is an anhydrous mixed solution of oleic acid and 1-octadecene;
[0021] (e): dispersing the nanoparticles obtained in (c) in a liquid, wherein the liquid is an anhydrous mixed solution of oleic acid and 1-octadecene;
[0022] (f): heating the liquid obtained in (b), and hot-injecting the liquid obtained in (e) at a high temperature, so that after the reaction, the sensitized doped inner shell layer is coated on the surface of the core layer nanoparticles to obtain double-layer nanoparticles;
[0023] (g): Dispersing alkaline earth metal trifluoroacetate and zirconium acetate in a liquid:
[0024] The alkaline earth metal trifluoroacetic acid salt is M(CF3COO)2 (M=Ca, Sr, Ba), and the liquid is an anhydrous mixed solution of oleic acid, oleylamine and 1-octadecene;
[0025] (h): Disperse the double-layer particles obtained in (f) in a liquid:
[0026] The liquid is an anhydrous mixed solution of oleic acid and 1-octadecene;
[0027] (i): The liquid obtained in (g) is heated and hot-injected into the liquid obtained in (h) at high temperature. After the reaction, a zirconium-doped alkaline earth metal inert shell layer is generated on the surface of the double-layer particles to obtain a composite structure bio-controllable degradable upconversion fluorescent nanoprobe.
[0028] Preferably, the method further comprises using a surfactant to synthesize the nanoparticles, wherein the surfactant comprises one or more of oleic acid, oleylamine, 1-octadecene, acetylene glycol, and lauric acid.
[0029] Preferably, in the mixed solution of steps (a) and (b), the volume ratio of oleic acid, oleylamine and 1-octadecene is 1:(1-3):(2-5);
[0030] In the mixed solution of steps (d), (e), (g) and (h), the volume ratio of oleic acid to 1-octadecene is 1:(1-3).
[0031] Preferably, the reaction temperature in step (c) is 180-230° C., and the reaction time is 1-10 minutes;
[0032] In steps (f) and (i), the reaction temperature is 250-280° C. and the reaction time is 45-90 minutes.
[0033] Preferably, in step (a), the metal fluoride is NaF, and the molar ratio of the metal fluoride to the mixed solution is 1:(5-20);
[0034] In step (b), the rare earth compound is Ln(CF3COO)3, and the molar ratio of the rare earth compound to the mixed solution is 1:(5-20);
[0035] In step (d), the molar ratio of Ln(CF3COO)3, M(CF3COO)2 and zirconium acetate is 4:(4-10):(1-5);
[0036] In step (g), the molar ratio of M(CF3COO)2 to zirconium acetate is 4:(1-5);
[0037] The molar ratio of the compound in step (d) (g) to the mixed solution is 1:(4-20).
[0038] The advantages of the present invention compared with the prior art are:
[0039] 1. Excellent biosafety and controllable degradability: The three-layer biodegradable nanoprobe proposed in the present invention is constructed by doping zirconium to form a degradable component. The zirconium doping makes the bonding between the alkaline earth metal fluoride shells weak and cannot form a stable composite structure. Therefore, in the living water environment, the probe shell will disintegrate. The decomposed small particles and ultra-small cores can be filtered by the living glomeruli and can be metabolized by the living body, thus avoiding the potential side effects caused by the long-term accumulation of traditional nanomaterials in the body. In addition, the shell thickness and the content of Zr in the shell can be adjusted to achieve good biosafety and controllable degradability. 4+ The doping amount makes the degradation rate adjustable and controllable;
[0040] 2. Excellent fluorescence brightness and stability: The present invention adopts a core-shell-shell three-layer structure design. The core particle is NaLnF4 composed of pure activator, and the inner shell is doped with a high concentration of sensitizer. Compared with conventional nanoparticles, the content of activator and sensitizer in the whole particle is greatly increased, and the outermost layer is coated with an inert shell layer, which minimizes the negative impact of the surface quenching effect on luminescence, making its upconversion luminescence intensity superior, and can be stored for a long time in a non-degradable environment;
[0041] 3. Simple synthesis process: Compared with other complex fluorescent probe preparation methods, the present invention adopts a combination of hot injection and thermal decomposition to build a core-shell structure layer by layer. Each step is carried out under relatively mild conditions, which not only improves production efficiency but also ensures the structural integrity and functional consistency of the nanoprobe. This simplified process is suitable for large-scale production and provides the possibility for further application and promotion;
[0042] 4. Broad application prospects: This nanoprobe not only has excellent biocompatibility and optical properties, but also has broad application potential, especially in the field of bio-optical imaging and detection. Its high luminescence brightness, deep tissue penetration, and good biosafety make it an ideal tool for biomedical imaging and disease diagnosis, and promote the application of fluorescent probes in clinical medicine. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 Schematic diagram of the preparation and degradation metabolic process of the core-shell-shell structured nanoparticles in Example 1.
[0044] Figure 2 This is a transmission electron microscope (TEM) image of the ultrasmall core nanoparticles in Example 1.
[0045] Figure 3 TEM electron microscope image of the core-shell-shell structured nanoparticles in Example 1 and the upconversion spectrum of degradation in water environment changing with degradation time.
[0046] Figure 4 TEM electron microscope image of the core-shell-shell structured nanoparticles in Example 2 and the upconversion spectrum of degradation in water environment changing with degradation time.
[0047] Figure 5 TEM electron microscope image of the core-shell-shell structured nanoparticles in Example 3 and the upconversion spectrum of degradation in water environment changing with degradation time.
[0048] Figure 6 The figure is a summary comparison of the degradation rates of Example 1, Comparative Example 1 and Comparative Example 2 over time. DETAILED DESCRIPTION
[0049] The present invention is further described in detail below in conjunction with the accompanying drawings.
[0050] The present invention is a method for preparing a biocontrollable degradation and metabolic upconversion fluorescent nanoprobe, which comprises the following steps:
[0051] The purpose of the present invention is achieved by the following technical solution: a method for preparing a bio-metabolizable upconversion fluorescent nanoprobe, comprising the following steps:
[0052] (1) Preparation of core layer NaLnF4 (Ln = Yb, Er, Tm, Ho) nanoparticles: NaF and Ln are reacted under high temperature conditions. 3+ The combination generates ultra-small NaLnF4 nanoparticles. The core layer nanoparticles are irregularly spherical in shape, with an average particle size of less than 5.5nm, and can be filtered by living glomeruli and metabolized by organisms.
[0053] (2) Preparation of sensitizer-doped inner shell layer MF2: Ln, Zr (M = Ca, Sr, Ba; Ln = Yb, Nd / Yb): The generated NaLnF4 nanoparticles are dispersed in an anhydrous mixed solution composed of a variety of surfactants, and then a mixed solution of Ln(CF3COO)3 (Ln = Yb, Yb / Nd), M(CF3COO)2 (M = Ca, Sr, Ba; Ln = Yb, Nd / Yb) and zirconium acetate is added. At high temperature, the outer layer of the core particle begins to grow a sensitizer-doped inner shell layer MF2: Ln, Zr to form double-layer particles with a particle size of about 10-30 nm. The sensitizer Ln in the sensitizer-doped inner shell layer 3+ When excited by near-infrared incident light of a certain power, the ions absorb photons and transfer energy to the activator ions in the core layer, enabling the double-layer particles to emit upconverted visible light.
[0054] (3) Preparation of inert outer shell MF2:Zr (M = Ca, Sr, Ba): The double-layer particles are dispersed again in an anhydrous mixed solution composed of multiple surfactants, and M(CF3COO)2 (M = Ca, Sr, Ba) and zirconium acetate are hot-injected. At high temperature, an MF2:Zr inert outer shell is formed on the surface of the double-layer particles, and the final three-layer core-shell structure nanoprobe is obtained, with a particle size of about 30-100nm. The third inert outer shell can further avoid the sensitizer Ln 3+ The quenching effect of ions and surface defects of double-layer particles significantly improves the upconversion fluorescence brightness.
[0055] Example 1
[0056] Example 1 presents a method for preparing a fluorescent nanoprobe for controllable degradation and metabolic upconversion in vivo. The probe consists of a multilayer core-shell structure, including a core layer, a sensitizer-doped inner shell layer, and an inert outer shell layer. The core layer uses cubic phase NaErF4 nanoparticles with an average particle size of about 3nm, which are irregular particles that are approximately spherical and have the characteristics of being rapidly metabolized by the glomerulus. The surface of the core layer is coated with a layer of Yb doped 3+ and Zr 4+ The CaF2:40% Yb, 10% Zr sensitizer doped inner shell layer has an average shell thickness of about 6nm, thus forming an activator core layer-sensitizer doped inner shell double-layer structure. The sensitizer absorbs photons under near-infrared excitation light, and the electrons transition from the ground state to the excited state, and transfer the energy to the activator ions in the core layer, so that the double-layer particles can emit up-conversion visible light. The outermost layer is coated with an inert outer shell layer CaF2:10% Zr with an average thickness of about 6nm, and finally forms a three-layer structure of core layer-sensitizer doped inner shell layer-inert outer shell layer. This outer shell layer effectively avoids the quenching effect between the sensitizer ions in the sensitizer doped inner shell layer and the surface defects of the double-layer particles.
[0057] The probe is excited by a 980nm continuous excitation light with a certain power. The photon energy of this wavelength is similar to that of Yb 3+ from 2 F 2 / 7 Energy level to 2 F 5 / 7 The ground state absorption of the energy level matches that of the Yb 3+ After absorbing a 980nm photon, Yb 3+ With Er 3+ There is an efficient energy transfer process between Yb 3+ middle 2 F 5 / 7 The particles at the energy level transfer energy to Er 3+ In the middle 4 I 15 / 2 The ground state energy level of the particle relaxes back to 2 F 2 / 7 Energy level, Er 3+ The ground state particles are excited to 4 I 11 / 2 energy level, it will fall back to 4 I 13 / 2 energy level, and then continue to absorb Yb 3+ The energy transferred jumps to a higher energy level, such as 4 F 9 / 2 , 4 F 7 / 2 and 4 G 7 / 2 Energy levels, and finally return to the ground state by radiation transition, releasing characteristic red light and characteristic green light, showing as bright yellow light.
[0058] In the living water environment, both the sensitizer-doped inner shell and the inert outer shell will gradually degrade, and the final product, together with the ultra-small core, passes through the filtration barrier of living kidney cells and is ultimately metabolized by the organism.
[0059] Example 2
[0060] In order to verify the controllable degradation characteristics of Example 1, a comparative example 1 with the same other conditions and different shell thickness was prepared. The structure of the comparative example 1 is consistent with that of Example 1, and the preparation steps are consistent with those described in Example 2. The difference is that when coating the sensitized doped inner shell layer and the inert outer shell layer, the amount of Ca(CF3COO)2 added is doubled, the reaction time is doubled, and the proportion of Yb and Zr elements therein is kept unchanged. The overall size of the comparative example 1 is about 35nm, which is 10nm different from that of Example 1. The comparative example 1 and Example 1 were placed in water at the same time, and irradiated with 980nm continuous light with a power of 50mw. The initial luminescence spectrum and the bright luminescence spectrum after 4 hours were observed and compared to verify the feasibility of regulating the degradation performance by the shell thickness. The peak intensity of each spectrum was recorded.
[0061] Example 3
[0062] In order to verify the controllable degradation characteristics of Example 1, a comparative example 2 with different zirconium doping contents under the same other conditions was prepared. The structure of the comparative example 2 was consistent with that of Example 1, and the preparation steps were consistent with those described in Example 2. The difference was that when the sensitized doped inner shell layer and the inert outer shell layer were coated, the content of zirconium acetate added was doubled, and the proportion of Yb elements and the thickness of the shell layer were kept unchanged. The overall size of the comparative example 2 was about 25nm, which was consistent with that of Example 1. The comparative example 2 and Example 1 were placed in water at the same time, and irradiated with 980nm continuous light with a power of 50mw. The initial luminescence spectrum was observed and compared with the bright luminescence spectrum after 4 hours to verify the feasibility of regulating the degradation performance by the thickness of the shell layer.
[0063] The present invention and its embodiments are described above, and such description is not restrictive. The drawings show only one embodiment of the present invention, and the actual structure is not limited thereto. In short, if ordinary technicians in the field are inspired by it, without departing from the purpose of the invention, they can design a structure and embodiment similar to the technical solution without creativity, which should belong to the protection scope of the present invention.
Claims
1. A design of a living controllable degradation and metabolic upconversion fluorescent nanoprobe structure, characterized by: It consists of a core layer, an inner shell layer and an outer shell layer, and the particle size is less than 100nm; The core layer is a nano-particle structure, the inner shell layer is an alkaline earth metal fluoride having a rare earth sensitizer and zirconium element, and the outer shell layer is an alkaline earth metal fluoride having zirconium element.
2. According to claim 1, the in vivo controllable degradation and metabolic upconversion fluorescent nanoprobe structure design is characterized by: The nanoparticle structure comprises cubic phase NaYF4 or NaLuF4 fluoride nanoparticles doped with a rare earth element activator, and the particle size is less than 5.5 nm.
3. The in vivo controllable degradation and metabolic upconversion fluorescent nanoprobe structure design according to claim 2 is characterized by: The rare earth element activator is one or a combination of ytterbium, thulium, holmium, erbium and praseodymium.
4. The in vivo controllable degradation and metabolic upconversion fluorescent nanoprobe structure design according to claim 1 is characterized by: The inner shell matrix is one or a combination of cubic calcium fluoride, strontium fluoride or barium fluoride; The inner shell rare earth sensitizer is one or a combination of ytterbium or neodymium.
5. A living body controllable degradation and metabolic upconversion fluorescent nanoprobe structure design according to any one of claims 1 to 4, characterized in that: When the core layer covers the inner shell layer, it becomes a double-layer particle with a particle size of 8 to 20 nm.
6. A living body controllable degradation and metabolic upconversion fluorescent nanoprobe structure design according to any one of claim 5, characterized in that: The outer shell layer is one or a combination of cubic calcium fluoride, strontium fluoride or barium fluoride. When the outer shell layer covers the double-layer particles, triple-layer particles are formed with a particle size of 10 to 100 nm.
7. A method for preparing a fluorescent nanoprobe structure design for in vivo controllable degradation and metabolic upconversion, applied to the fluorescent nanoprobe structure design described in any one of claims 1 to 6, characterized in that: The following steps are involved: (a): Disperse metal fluoride in liquid: The metal fluoride is a mixture of NaF or NaOH and NH4F, and the liquid is an anhydrous mixed solution of oleic acid, oleylamine and 1-octadecene; (b): Dispersing the rare earth compound in a solvent: The rare earth compound is one or more of Ln(CF3COO)3, Ln(CH3COO)3, LnCl3, wherein (Ln=Yb, Er, Tm, Ho); The solvent is an anhydrous mixed solution of oleic acid, oleylamine and 1-octadecene; (c): heating the liquid obtained in (b) and hot-injecting the liquid obtained in (a) at high temperature to obtain rare earth activator-doped core layer nanoparticles after reaction; (d) Dispersing the sensitizer trifluoroacetate, alkaline earth metal trifluoroacetate and zirconium acetate in a liquid: The sensitizer trifluoroacetate is Ln(CF3COO)3(Ln=Yb,Nd), the alkaline earth metal trifluoroacetate is M(CF3COO)2(M=Ca,Sr,Ba), the chemical formula of zirconium acetate is: Zr(CH3COO)4, and the liquid is an anhydrous mixed solution of oleic acid and 1-octadecene; (e): dispersing the nanoparticles obtained in (c) in a liquid, wherein the liquid is an anhydrous mixed solution of oleic acid and 1-octadecene; (f): heating the liquid obtained in (b), and hot-injecting the liquid obtained in (e) at a high temperature, so that after the reaction, the sensitized doped inner shell layer is coated on the surface of the core layer nanoparticles to obtain double-layer nanoparticles; (g): Dispersing alkaline earth metal trifluoroacetate and zirconium acetate in a liquid: The alkaline earth metal trifluoroacetic acid salt is M(CF3COO)2 (M=Ca, Sr, Ba), and the liquid is an anhydrous mixed solution of oleic acid, oleylamine and 1-octadecene; (h): Disperse the double-layer particles obtained in (f) in a liquid: The liquid is an anhydrous mixed solution of oleic acid and 1-octadecene; (i): The liquid obtained in (g) is heated and hot-injected into the liquid obtained in (h) at high temperature. After the reaction, a zirconium-doped alkaline earth metal inert shell layer is generated on the surface of the double-layer particles to obtain a composite structure bio-controllable degradable upconversion fluorescent nanoprobe.
8. The method for preparing a living body controllable degradation and metabolic upconversion fluorescent nanoprobe structure design according to claim 7, characterized in that: The method also includes synthesizing nanoparticles using a surfactant, wherein the surfactant includes one or more of oleic acid, oleylamine, 1-octadecene, acetylene glycol, and lauric acid.
9. The method for preparing a living body controllable degradation and metabolic upconversion fluorescent nanoprobe structure design according to claim 7, characterized in that: In the mixed solution of steps (a) and (b), the volume ratio of oleic acid, oleylamine and 1-octadecene is 1:(1-3):(2-5); In the mixed solution of steps (d), (e), (g) and (h), the volume ratio of oleic acid to 1-octadecene is 1:(1-3).
10. The method for preparing a living body controllable degradation and metabolic upconversion fluorescent nanoprobe structure design according to claim 7, characterized in that: In step (c), the reaction temperature is 180-230° C. and the reaction time is 1-10 minutes; In steps (f) and (i), the reaction temperature is 250-280° C. and the reaction time is 45-90 minutes.
11. The method for preparing a living body controllable degradation and metabolic upconversion fluorescent nanoprobe structure design according to claim 7, characterized in that: In the step (a), the metal fluoride is NaF, and the molar ratio of the metal fluoride to the mixed solution is 1:(5-20); In step (b), the rare earth compound is Ln(CF3COO)3, and the molar ratio of the rare earth compound to the mixed solution is 1:(5-20); In step (d), the molar ratio of Ln(CF3COO)3, M(CF3COO)2 and zirconium acetate is 4:(4-10):(1-5); In step (g), the molar ratio of M(CF3COO)2 to zirconium acetate is 4:(1-5); The molar ratio of the compound in step (d) (g) to the mixed solution is 1:(4-20).